Identifikasi Citra Untuk Mengidentifikasi Jenis Daging Sapi Menggunakan Transformasi Wavelet Haar - Kiswanto Kiswanto; Eko Sediyono; Suhartono Suhartono (Universitas Diponegoro, 2014)
In this research, conducted research on the identification of the image to identify the type of ground beef using the Haar wavelet transform. The study was intended To check the performance of Haar wavelet in identifying the types of beef. The process of image processing is done by calculating the value of R, G and B in each image of the meat, then do the normalization process to get the index value of R, G and the index B index and do the conversion from RGB to a model of HSI models to get the magnitude of the hue, saturation and intensity. The resulting value of the image processing used as input parameter verification program. The highest accuracy produced by the Haar wavelet is 80% on the kind of fresh beef, fresh frozen beef, beef rotten, rotten dried beef, while the lowest accuracy was 0% for frozen beef rotten.Keywords: Identification; Haar Wavelet Transformation